Development of a Simple Preoperative Risk Score for Persistent Pain After Breast Cancer Surgery: A Prospective Observational Cohort Study. Issue 6 (June 2018) - Dereu, Domitille; Savoldelli, Georges L.; Combescure, Christophe; Mathivon, Stanislas; Rehberg, Benno
Abstract : Objectives: Persistent postoperative pain is reported by 30% to 50% of patients following breast cancer surgery. Studies testing preventive measures, however, have so far failed to produce consistent positive results. If preventive measures could be targeted to a subgroup of patients at high risk of persistent pain, positive results would be more likely. Our aim was to develop a simple risk score predicting persistent pain after breast cancer surgery. Materials and Methods: In a prospective observational cohort study, we tested the predictive ability of a 4 simple items score for persistent pain in 200 patients scheduled for breast cancer surgery. A multivariable logistic regression model was created for the outcome of clinically important pain at 4 months. Results: On the basis of literature review and univariable analysis of our data, 4 parameters were selected: preoperative pain at the surgical site, history of depression, age below 50 years and expected pain of high intensity (>6/10). Points for the score are based on the coefficients of the logistic regression model. A total score ≥2 points/5 predicts a risk of developing clinically important pain at 4 months >30%, with an area under the curve-receiver operating characteristic of 0.81. Discussion: We studied known risk factors for persistent pain in patients scheduled for breast cancer surgery and constructed a preoperative risk score simple enough to select high-risk patients in future prevention studies. Abstract : Supplemental Digital Content is available in the text.